Distal Patellar Tendon Avulsion Associated with an ACL Tear in a Teenager: A Case Report and Review of the Literature - Christina Steiger; Benoit Coulin; Tanguy Vendeuvre; Anne Tabard-Fougere; Giacomo De Marco; Céline Habre; Romain Dayer; Dimitri Ceroni (Case Reports in Orthopedics)
Distal patellar tendon avulsions are rare injuries in healthy individuals, and to date, no case affecting skeletally mature teenagers and adolescents has been reported. In the majority of cases, distal patellar tendon avulsions are associated with severe intra-articular knee lesions, signifying a high-energy trauma. We present the case of a 15.5-year-old female who was admitted to the emergency department after a knee injury. The mechanism of injury was a combination of landing after a jump off a scooter and sudden deceleration with a fixed foot. Lateral radiographs revealed a distal patellar tendon avulsion. An MRI was conducted to accurately diagnose concomitant lesions. The MRI revealed a complete tear of the ACL, and associated bone bruises on the lateral femoral condyle, and also on the posterolateral tibial plateau. A knee joint exam under general anesthesia demonstrated good stability during valgus stress testing and only a grade 1 positive Lachman test. Therefore, we decided to only reconstruct the extensor mechanism and to abstain from a primary ACL reconstruction. The presented case and review of the literature demonstrate the clinical relevance of this atypical lesion. In fact, a distal patellar tendon avulsion after physeal fusion of the proximal tibia should raise a strong suspicion of severe associated intra-articular knee lesions and requires prompt MRI investigation. However, controversy still exists regarding the management of these injuries, in particular concerning the question of whether to address both injuries in a single stage or in 2 stages.